Utilização da folha de batata doce biofortificada na produção de revestimento comestível para conservação pós-colheita de tomate - Souza, Diane Maschio de (2023)
Sweet potatoes produce various by-products based on processing and desired outcome. In agriculture, residues are obtained by removing branches and leaves from the field. These residues are rich in carbohydrates, proteins, vitamins, and minerals, which can be used as raw materials for the products manufactured with high nutritional value. Given the above, the purpose of the present work was to extract, characterize and verify the effectiveness of concentrated protein from the Ipomoea batatas Beauregard (SPLPC) leaves in the development of edible coatings, applying the coating on Saladete tomatoes. Leaf protein was extracted by ultrasound-assisted isoelectric precipitation and hydrolyzed by pepsin (H-pep) and pancreatin (H-pan) enzymes, exposed to a hydrolysis time of 60, 120, 180 and 240 min. The solubilization functional properties, foaming and emulsification were evaluated in the peptides produced in the first experimental stage (enzymatic hydrolysis), which directly reflect on the processing and shelf life of foods. Proteins and their hydrolysates can be used as raw material for innovative packaging with biopolymers, used as an edible coating that can be applied to the fruits’ surfaces. In the present study, tomato (Solanum lycopersicum L.) was used to apply the edible coating. For the biopolymer development, two polysaccharides were evaluated: pectin (P) and sodium alginate (SA), added with sweet potato leaf protein concentrate SPLPC and yeast Meyerozyma caribbica (Y), whose function was to protect the fruit when exposed to the fungus Alternaria spp. The polysaccharide that obtained the best results in the characterization was tested in relation to the effect on the quality tomatoes properties. As main results, it can be highlighted that the SPLPC presented 57.78% protein and an average extraction yield of 18%. The yield and protein content of H-pep and H-pan increased significantly (p<0.05) as a hydrolysis time function, between the two tested enzymes. H-pan was more efficient than H-pep to produce hydrolysates from SPLPC. This difference can be attributed to the enzymes used, the hydrolysis conditions and the amino acid SPLPC composition. SPLPC enzymatic hydrolysis promoted significant improvements in the functional proteins extracted characteristics from sweet potato leaves. Regarding the edible coating, the polysaccharides formed with sodium alginate showed more satisfactory results when compared to formulations with pectin. The combination of SA and SPLPC improved the coating properties, lowering moisture and water vapor permeability, increasing solubility, thickness and making the edible coatings yellowish in color. In general, the biopolymers evaluated as edible coatings achieved the proposed objective, acting in a way to delay food deterioration, prolonging the processing of beneficial effects and maintaining the quality and safety of foods with a shelf-life extension.